Wind-induced vibration control and parametric optimization of connected high-rise buildings with tuned liquid-column-damper–inerter. (1st January 2021) - Wang, Qinhua; Tian, Huarui; Qiao, Haoshuai; Tiwari, Nayan Deep; Wang, Quan
Highlights: A model for adjacent high-rise buildings linked with a TLCDI is established under wind loads. Mitigation effects of the TLCDI on wind-induced responses are investigated based on landmark high-rise buildings. The TLCDI with less mass than TLCDs dramatically decreases wind-induced acceleration responses of the landmark buildings. Abstract: A novel passive control device, defined as tuned liquid-column-damper–inerter (TLCDI), with nonlinear characteristics is developed for control of the wind-induced responses of adjacent high-rise buildings. TLCDI exploits the combined advantages of liquid sloshing inside TLCD container as well as mass amplification effects of the inerter to control the wind induced responses. Firstly, a model for adjacent high-rise buildings linked by a TLCDI is established subjected to wind loading. Subsequently, an equivalent linearization method is used to study the model, and the results are verified by a numerical method. Finally, mitigation effects of the TLCDI with optimal designs on wind-induced responses are investigated by comparison studies with the results of two tuned liquid column dampers (TLCDs) installed on benchmark buildings. The results indicate that the TLCDI, which is much lighter than two TLCDs, dramatically decreases the wind-induced acceleration responses of the linked buildings by 37.7% (Building-1) and 42.0% (Building-2) at the across-wind direction (90° wind direction).